UPAYA MENINGKATKAN HASIL BELAJAR PKn MELALUI MODEL PEMBELAJARAN SCRAMBLE SISWA DI SDN 13 MUARA KUANG - Samsidar, Samsidar (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
The research subjects were grade V students of SD Negeri 13 Muara Kuang, totaling 17 students. Methods of data collection in the form of tests, observations, and documentation. The data analysis technique used is descriptive quantitative and qualitative. The indicators of the success of the action are marked by 75% of the number of students who take part in the learning process that have obtained KKM scores. Based on the results of the tests in the implementation of learning with a scramble model, students who achieved a value of ≥75 were 70.59% in the first cycle and increased to 88.24% in the second cycle. The action was dismissed in the second cycle because it had reached the criteria of success.